Post‐MI free wall rupture syndrome. Case report, literature review, and new terminology. Issue 6 (6th May 2016) - Che, Jingjin; Li, Guangping; Chen, Kangyin; Liu, Tong
Key Clinical Message: Common clinical features of subacute rupture left ventricular free wall after acute ST segment elevation myocardial infarction are: (1) recurrent or persistent chest pain; (2) recurrent or persistent ST segment elevation; (3) hypotension. Integrating these signs into a syndrome can increase the clinician's awareness to the fatal complication. Abstract : Common clinical features of subacute rupture left ventricular free wall after acute ST segment elevation myocardial infarction are: (1) recurrent or persistent chest pain; (2) recurrent or persistent ST segment elevation; (3) hypotension. Integrating these signs into a syndrome can increase the clinician's awareness to the fatal complication.